HvPap-1 C1A protease actively participates in barley proteolysis mediated by abiotic stresses - Velasco-Arroyo, Blanca (Journal of experimental botany, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.